Adulterants present in the San Diego county fentanyl supply: a laboratory analysis of seized law enforcement samples - Henrik Galust; Justin A. Seltzer; Jeremy R. Hardin; Nathan A. Friedman; Jeff Salamat; Richard F. Clark; Jennifer Harmon (BMC, 2024)
Abstract Background The opioid overdose crisis is one of the worst public health crises ever to face the US and emerging evidence suggests its effects are compounded by the presence of drug adulterants. Here we report our efforts to characterize the adulterants present within the local fentanyl supply of San Diego County, obtained from undifferentiated drug samples seized by local law enforcement over the calendar year 2021. Methods Thirty-two participating local law enforcement agencies across San Diego submitted 4838 unknown individual illicit drug samples (total of 312 kg) to the San Diego County Sheriff's Department Regional Crime Laboratory for identification. Results Qualitative analysis of these samples via FTIR and GC-MS identified methamphetamine (38.7%), fentanyl (20.8%), diacetylmorphine (heroin) (10.2%), codeine (5.8%) and alprazolam (4.3%) as the most common illicit substances and the presence of 52 unique adulterants. The most common adulterants included 4-methylaminoantipyrine (4-MAAP) (10.9%), mannitol (9%), acetaminophen (8.5%), methamphetamine (4.2%), diacetylmorphine (heroin) (3.6%), tramadol (1.9%), and xylazine (1.7%). Several additional pharmacologically active adulterants and contaminants of interest were also identified. Conclusion This analysis is vital for public health use and harm reduction efforts at the level of the individual consumer. Continued direct surveillance of the drug supply is necessary for the detection of potentially harmful adulterants that may pose serious threats to the public.